2022
DOI: 10.1037/rel0000397
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity, spirituality, and obsessive-compulsive disorder-related symptoms in clinical and nonclinical samples.

Abstract: Despite speculation that highly religious individuals may be predisposed toward developing obsessivecompulsive disorder (OCD), results regarding the relationship between religiosity and spirituality and OCD symptoms are mixed. Limitations of the literature include the use of measures with unknown psychometric properties that do not differentiate between facets of religiosity, a limited range of religious affiliations, and predominant use of undergraduate samples. The current study attempted to clarify the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Historically, studies have not included religious scrupulosity in analyses, which, based on the current study, confounds the relation between religiosity and mental health if not controlled. Our findings are in line with more recent studies highlighting the importance of accounting for both religiosity and religious scrupulosity when measuring mental health impairment (e.g., Henderson et al, 2022). Yet, our findings extend the current literature base by examining these relations specifically in Latinx individuals, using more complex statistical analyses to more accurately account for the multifaceted relation between religiosity, religious scrupulosity, clinical impairment, and covariates in this population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Historically, studies have not included religious scrupulosity in analyses, which, based on the current study, confounds the relation between religiosity and mental health if not controlled. Our findings are in line with more recent studies highlighting the importance of accounting for both religiosity and religious scrupulosity when measuring mental health impairment (e.g., Henderson et al, 2022). Yet, our findings extend the current literature base by examining these relations specifically in Latinx individuals, using more complex statistical analyses to more accurately account for the multifaceted relation between religiosity, religious scrupulosity, clinical impairment, and covariates in this population.…”
Section: Discussionsupporting
confidence: 93%
“…One such study showed a distinction between religiosity and religious scrupulosity in a large sample ( n = 746) of community members of various religious denominations (e.g., Catholic, Protestant, Orthodox Christian, Buddhist, Hindu, Muslim, Sikh, Jewish, Agnostic, Spiritual, Atheist), such that obsessional thinking was significantly positively associated with religious scrupulosity ( r = .56) but not religious fundamentalism ( r = .06). However, only eight people in the sample identified as Hispanic, Latin American, or European Hispanic, and statistical techniques used (i.e., bivariate correlations) may not account for the complex relation between variables (Henderson et al, 2022). Considering the influence of religion in Latinx culture, and the impact of culture on symptom profiles (Rosa-Alcázar & Iniesta-Sepúlveda, 2018), the present study specifically investigated whether the relation between religiosity, religious scrupulosity, and mental health impairment extends to the Latinx population.…”
mentioning
confidence: 99%
“…However, if unwanted religious thoughts are accompanied with beliefs about the importance of those thoughts and an intolerance of uncertainty (e.g., thought-action fusion; Shafran et al 1996), they may develop into clinical obsessions (Abramowitz and Jcoby 2014). This indicates that scrupulosity could constitute a dimension origin in common religious struggle or doubts (Henderson et al 2022), which may develop into a pathological presentation as OCD disorder in the presence of risk factors associated with poor insight and avoiding uncertainty (Tolin et al 2001).…”
Section: Scrupulositymentioning
confidence: 99%
“…Treatment results of OCD with scrupulosity symptoms are poor, which is attributed mainly to lack of knowledge about the nature of religious obsession among clinicians but also due to a reinforcement of clients' obsessions by members of their religious community (Huppert and Siev 2010). However, scrupulosity also appears with a different intensity in people without a clinical diagnosis of OCD (Abramowitz et al 2002;Henderson et al 2022). This indicates that scrupulosity could be regarded as a phenomenon of the intersection between common religious/spiritual experiences and clinically-relevant obsessive thoughts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation